From Connemara to Gukurahundi genocide of the 1980s in Zimbabwe - Joshua Chakawa (Unisa Press, 2023)
The article addresses new and emerging perspectives on Gukurahundi genocide as remembered by combatants who participated or were close to the violent clashes between former Zimbabwe African National Liberation Army (ZANLA) and Zimbabwe People’s Revolutionary Army (ZIPRA) guerrillas at Connemara and how their fighting resulted in a national crisis. The bulk of the literature on this subject so far has concentrated on atrocities committed by 5 Brigade and other government forces in Matabeleland and the Midlands provinces between 1983 and 1987 without elaborating how it all began. This article unearths causes and course of the violence at Connemara, how it was organised and deployment of government security forces to quell it together with how the violence then spread to other barracks. The purpose of the study is to contribute interpretations and debate on this mass killing which today continues to haunt Zimbabwe. Connemara was chosen as a case study because fighting there between former ZANLA and ZIPRA guerrillas went unchecked and finally led to desertions in the army and then the Gukurahundi genocide. The story being told here is unique in the sense that it does not speak to civilian victims of violence but rather to armed men who were involved or at least close to the event. In gathering data, use was also made of secondary sources both published and unpublished. In terms of reconciliation and healing, it is important to take into consideration a multiplicity of voices, which is precisely what this article is doing.